2013
DOI: 10.1002/eco.1392
|View full text |Cite
|
Sign up to set email alerts
|

A Littoral Fauna Index for assessing the impact of lakeshore alterations in Alpine lakes

Abstract: Lakeshore deterioration is a major threat to the ecological integrity of lakes worldwide. In this study, the relationship between littoral benthic invertebrates and the Lakeshore Modification Index (LMI) was examined. The influence of the taxonomic resolution on littoral benthic invertebrate community response to LMI was assessed using the results of the canonical correspondence analysis and the relationship between the taxa richness, Shannon–Wiener diversity index and the LMI. Benthic invertebrates were sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
(101 reference statements)
0
25
0
Order By: Relevance
“…In Slovenia, studies with LMI focusing mainly on human impact confirmed a relationship between lake-shore modification and benthic invertebrate taxa (Šiling & Urbanič, 2016;Urbanič, 2014;Urbanič et al, 2012). A more comprehensive study was conducted in Italy, as a part of an EU LIFE+ project (LIFE08 ENV/IT/000413 INHABIT) covering 12 representative lakes (including reservoirs) in Piedmont and…”
Section: Integration With Biological Quality Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Slovenia, studies with LMI focusing mainly on human impact confirmed a relationship between lake-shore modification and benthic invertebrate taxa (Šiling & Urbanič, 2016;Urbanič, 2014;Urbanič et al, 2012). A more comprehensive study was conducted in Italy, as a part of an EU LIFE+ project (LIFE08 ENV/IT/000413 INHABIT) covering 12 representative lakes (including reservoirs) in Piedmont and…”
Section: Integration With Biological Quality Elementsmentioning
confidence: 99%
“…Many of the hydromorphological characteristics that influence macrophytes in lakes will, by extension, affect other organisms, such as invertebrates. Yet, there are relatively few studies that directly link macroinvertebrate communities in lakes to hydromorphological factors (but see McGoff et al, ; Peterlin & Urbanič, ; Smith, Maitland, & Pennock, ; Urbanič, ; Urbanič, Petkovska, & Pavlin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In calculation of highest and lowest environmental group specific species score, extremes and outliers were not considered. In order to determine the relationship between recognized environmental gradients and littoral benthic assemblage structure in more detail, we determined taxa tolerance values that are frequently used in bioassessment (e.g., Zelinka and Marvan, 1961;Urbanič, 2014b). We determined tolerance values using the pCCA ordination axis species tolerance (root mean squared deviation for species) according to 3 Results…”
Section: Groupmentioning
confidence: 99%
“…Settlement on lake shores and numerous activities makes the littoral a highly threatened zone in lakes (Vadeboncoeur et al, 2001;Jenkins, 2003;Peterlin and Urbanič, 2013). Anthropogenic disturbances, such as eutrophication (White and Irvine, 2003;Donohue et al, 2009b;Bazzanti et al, 2012), fish stocking (Pierce and Hinrichs, 1997;Leppä et al, 2003), hydromorphological alterations (Gabel et al, 2012;Jurca et al, 2012;Peterlin and Urbanič, 2013;McGoff et al, 2013;Urbanič, 2014b) and land use (McGoff and Sandin, 2012), may have profound effects more on the littoral zone than the profundal, and thus warrant closer considerations in lake assessments.…”
Section: Introductionmentioning
confidence: 99%